Multi-omics analysis revealed the differential effects and mechanisms of PFOA and OBS exposure on liver and intestinal function - Minjie Yu; Ruochen Ren; Hongbo Zeng; Meng Hou; Kaiyi Jiang; Caihong Hu; Yingping Xiao; Wentao Lyu (Molecular & Cellular Toxicology, 2026)

Serum metabolomic analysis in mice exposed to perfluorooctanoic acid and sodium p-perfluorous nonenoxybenzene sulfonate - Yuting Xu; Ruochen Ren; Minjie Yu; Wentong Zheng; Yang Wen; Zhen Wang; Hongbo Zeng (Molecular & Cellular Toxicology, 2025)

A comprehensive review and future research directions of ensemble learning models for predicting building energy consumption - Zeyu Wang; Yuelan Hong; Luying Huang; Miaocui Zheng; Hongping Yuan; Ruochen Zeng (Energy and Buildings, 2025)

An overall consistent increase of global aridity in 1970–2018 - Dengnan Luo; Zhongmin Hu; Licong Dai; Guolong Hou; Kai Di; Minqi Liang; Ruochen Cao; Xiang Zeng (Journal of Geographical Sciences, 2023)

Identifying the optimal heterogeneous ensemble learning model for building energy prediction using the exhaustive search method - Zeyu Wang; Zhixi Liang; Ruochen Zeng; Hongping Yuan; Ravi S. Srinivasan (Energy and Buildings, 2023)

The global decline in the sensitivity of vegetation productivity to precipitation from 2001 to 2018 - Xiang Zeng; Zhongmin Hu; Anping Chen; Wenping Yuan; Guolong Hou; Daorui Han; Minqi Liang; Kai Di; Ruochen Cao; Dengnan Luo (Global Change Biology, 2022)
The sensitivity of vegetation productivity to precipitation ( S ppt ) is a key metric for understanding the variations in vegetation productivity under changing precipitation and predicting future changes in ecosystem functions. However, a comprehensive assessment of S ppt over all the global land is lacking. Here, we investigated spatial patterns and temporal changes of S ppt across the global land from 2001 to 2018 with multiple streams of satellite observations. We found consistent spatial patterns of S ppt with different satellite products: S ppt was highest in dry regions while low in humid regions. Grassland and shrubland showed the highest S ppt , and evergreen needle‐leaf forest and wetland showed the lowest. Temporally, S ppt showed a generally declining trend over the past two decades ( p S ppt was especially noticeable in North America and Europe, likely due to the increase in precipitation. In central Russia and Australia, however, S ppt showed an increasing trend. Biome‐wise, most ecosystem types exhibited significant decrease in S ppt , while grassland, evergreen broadleaf forest, and mixed forest showed slight increases or non‐significant changes in S ppt . Our finding of the overall decline in S ppt implies a potential stabilization mechanism for ecosystem productivity under climate change. However, the revealed S ppt increase for some regions and ecosystem types, in particular global grasslands, suggests that grasslands might be increasingly vulnerable to climatic variability with continuing global climate change.

Maximum July–September temperatures derived from tree‐ring densities on the western Loess Plateau, China - Huiming Song; Ruochen Mei; Yu Liu; Daniel Nievergelt; Anne Verstege; Paolo Cherubini; Ruoshi Liu; Changfeng Sun; Qiang Li; Ling Chen; Xueli Zeng; Junqin Guo (International Journal of Climatology, 2021)
Tree‐ring densitometric studies conducted in semi‐arid regions are exceedingly rare. In this study, we evaluate a new maximum latewood density chronology from a collection of Picea purpurea trees growing in semi‐arid northwestern China for climatic reconstruction purposes. We find statistically significant correlations between annual maximum density variations and July–September maximum temperatures over the 1957–2014 calibration period. Using a linear model to transfer the density variations to temperature estimates, we then reconstruct maximum summer temperatures from 1840 to 2014. Statistical analyses and verification tests demonstrate that the resulting transfer function is both reliable and stable. The reconstructed temperature series shows strong inter‐annual and decadal variability. Several extremely cool and warm years are apparent on an inter‐annual scale, while three extended cool periods and a warm period are observed on a decadal scale. In addition, the reconstructed temperature series exhibits a pattern synchronous with that of the Indian monsoon index, as well as a moderate relationship to volcanic eruptions. This densitometric study reveals typical climatic variation characteristics and provides useful data for deepening our understanding of climate history in the semi‐arid regions of China.